Responsiveness to anti-tumour necrosis factor α therapy is related to pre-treatment tissue inflammation levels in rheumatoid arthritis patients. Issue 4 (27th November 2007) - van der Pouw Kraan, T C; Wijbrandts, C A; van Baarsen, L G; Rustenburg, F; Baggen, J M; Verweij, C L; Tak, P P
Abstract : Objective: The response of rheumatoid arthritis (RA) patients to treatment with neutralising antibodies to tumour necrosis factor α (TNFα) is highly variable. The underlying mechanism for therapy responsiveness is currently unknown. We therefore evaluated the relationship between baseline molecular profiles of synovial tissues from RA patients and the clinical response to treatment with infliximab. Methods: Synovial biopsies were obtained by arthroscopy from 18 RA patients with active disease (28 joint count Disease Activity Score (DAS28)⩾3.2) before initiation of treatment with infliximab. All patients were on stable methotrexate treatment. Clinical response at 16 weeks was defined as a reduction in DAS28 of ⩾1.2, non-response as reduction in DAS28 <1.2. Large-scale gene expression profiling using microarrays was performed on synovial tissue samples. To identify biological processes in synovial biopsies that could discriminate between responders and non-responders, we performed pathway analysis on the expression profiles. Results: A total of 12 patients responded to therapy, while 6 patients failed to fulfil the response criteria. We identified several biological processes, related to inflammation, which were up-regulated in patients who responded to therapy, compared to those who did not show clinical improvement. Conclusion: These results indicate that patients with a high level of tissue inflammation are more likely to benefit from anti-TNFα treatment.